Russian and Indian preschool educators’ beliefs about play activities: a comprehensive study - Veraksa, Aleksander; Chursina, Apollinaria; Singh, Purnima; Ramakrishna, Madhumita; Jain, Nishtha (Frontiers in Education, 2023)
In this study, preschool teachers beliefs regarding the play in preschool children in its various forms (role-play, rough-and-tumble play, digital play), the process of its development in children groups on samples of Russian and Indian educators were examined. 3013 respondents (all females), aged 18 to 77 (M=41.57; SD=10.02) from Russia and 116 respondents (10.34% males), aged 23 to 50 (M=36; SD=9) from India participated in the study. An original questionnaire aimed at assessment of attitudes towards different types of play in preschool educators was used. This instrument consisted of various sections which were focused on the understanding of play and it’s place in the everyday routine of the child group, role-play patterns characteristics (i.e., preferred plots, play materials, course of the play), rough-and-tumble play practice, attitudes towards digital play, and educators’ play competence (self-assessment regarding difficulties with joining the play, suggesting a plot or materials for play, etc.). Our main finding is that although the vast majority of educators in both cultures recognize the value of play for child development, this belief does not find practical expression in the daily life of the children's group. Our data showed that Indian educators are more likely to be a mediator of children's experience in play, while their Russian counterparts are more likely to be engaged in the role-play with children. The content characteristics of play among children in Russia and India were also described. There are differences in attitudes towards digital play: more experienced teachers have a more positive attitude towards the activities of children with digital devices, they see opportunities for the development of a child in the digital play. At the same time, those teachers in whose groups children enter into a digital play, teachers not only have a positive attitude towards this type of play, but also evaluate themselves more positively in the process of playing with children.